Ludic, co-design and tools supporting smart learning ecosystems and smart education : Proceedings of the 5th International Conference on Smart Learning Ecosystems and Regional Development /: Proceedings of the 5th International Conference on Smart Learning Ecosystems and Regional Development. ([2021]) - Unknown
No abstract available